Clinical characteristics and quality‐of‐life in patients surviving a decade of prostate cancer with bone metastases. (14th July 2015) - Klaff, Rami; Berglund, Anders; Varenhorst, Eberhard; Hedlund, Per Olov; Jǿnler, Morten; Sandblom, Gabriel; ,
Abstract : Objective: To describe characteristics and quality‐of‐life (QoL), and to define factors associated with long‐term survival in a subgroup of patients with prostate cancer with M1b disease. Patients and Methods: The study was based on 915 patients from a prospective randomised multicentre trial (No. 5) by the Scandinavian Prostate Cancer Group, comparing parenteral oestrogen with total androgen blockade. Long‐term survival was defined as patients having an overall survival of ≥10 years, and logistic regression models were constructed to identity clinical predictors of survival. QoL during follow‐up was assessed using the European Organisation for Research and Treatment of Cancer Quality‐of‐Life Questionnaire – C30 version 1 (EORTC‐C30) ratings. Results: In all, 40 (4.4%) of the 915 men survived for >10 years. Factors significantly associated with increased likelihood of surviving for >10 years in the univariate analyses were: absence of cancer‐related pain; Eastern Cooperative Oncology Group (ECOG) performance status of <2; negligible analgesic consumption; T‐category of 1–2; prostate‐specific antigen (PSA) level of <231 μg/L; and a Soloway score of 1. In the multivariate analyses, ECOG performance status of <2, PSA level of <231 μg/L, and Soloway score of 1, were all independent predictors of long‐term survival. All subscales of the EORTC‐C30 were higher in this group than for patients with short survival, but slowly declined over the decade. Conclusion: A subgroup of patients with prostate cancer with M1b disease and certain characteristics showed a positive long‐term response to androgen‐deprivation therapy with an acceptable QoL over a decade or more. Independent predictors of long‐term survival were identified as ECOG performance status of <2, limited extent of bone metastases (Soloway score of 1), and a PSA level of <231 μg/L at the time of enrolment.